P, Q, and R branches of the pure oxygen A-band at 762 nm - AL-Jalali, Muhammad Ahmad (International Journal of Physical Research, 2025)
Oxygen A-band absorption spectra exhibit interference between O2 monomer (with a discrete line at 762 nm) and O2 dimol (which ‎also exhibits a band spectrum at 762 nm) absorption. Analysis of the absorbance spectrum between 750 nm and 770 nm reveals ‎P, Q, and R branches, characteristic of rovibrational transitions. Pure oxygen spectra were analyzed at pressures ranging from 1 to 25 bar and at temperatures of 298 K, 323 K, 348 K, and 373 K using advanced data analysis methods. Integrated absorbance, Gaussian and ‎Lorentzian full width at half maximum height (FWHM), and maximum absorbance peak positions were calculated for the R and ‎P branches, and relevant formulas were deduced.